2016
DOI: 10.1166/jbmb.2016.1585
|View full text |Cite
|
Sign up to set email alerts
|

Soil Burial Degradation of Oil Palm Shell (OPS) Nanofiller and Phenol Formaldehyde (PF) Resin-Impregnated Oil Palm Trunk Lumber (OPTL): Dimensional Stability and Mechanical Properties

Abstract: In the present study, oil palm trunk lumber (OPTL) was chemically modified by impregnation with oil palm shell (OPS) nanofiller and phenol formaldehyde (PF) resin as a bulking agent (polymer matrix). A vacuum-pressure technique was used to impregnate OPTL stakes with phenol formaldehyde (PF) and OPS nanoparticles at 1, 3, 5, and 10% w/w. The resulting composite materials were buried in soil according to the BS EN ISO 846 standard for 6 and 12 months. After the designated burial period, structural and morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Sampel BKS dipilih dari bagian bawah batang pohon yaitu sekitar 1-2 meter dari permukaan tanah, dari bagian batang luar (Gambar 2), diambil dari bagian periferal BKS dan kemudian dipotong-potong dengan dimensi panjang x lebar x tebal adalah (15 × 5 × 5) cm. Semua sampel uji dikeringkan dalam oven pada suhu 60℃ selama 24 jam untuk mencegah penyusutan dilanjutkan dengan pengeringan dalam oven pada suhu (1032)°C selama 24 jam hingga mencapai kadar air sampel kurang dari 10% untuk siap dimodifikasi [22]. Sampel-sampel kering disimpan pada suhu kamar sebelum diberi perlakuan.…”
Section: Metodologi Persiapan Sampelunclassified
“…Sampel BKS dipilih dari bagian bawah batang pohon yaitu sekitar 1-2 meter dari permukaan tanah, dari bagian batang luar (Gambar 2), diambil dari bagian periferal BKS dan kemudian dipotong-potong dengan dimensi panjang x lebar x tebal adalah (15 × 5 × 5) cm. Semua sampel uji dikeringkan dalam oven pada suhu 60℃ selama 24 jam untuk mencegah penyusutan dilanjutkan dengan pengeringan dalam oven pada suhu (1032)°C selama 24 jam hingga mencapai kadar air sampel kurang dari 10% untuk siap dimodifikasi [22]. Sampel-sampel kering disimpan pada suhu kamar sebelum diberi perlakuan.…”
Section: Metodologi Persiapan Sampelunclassified
“…Several studies have investigated the wood quality enhancement by using resin impregnation (Deka et al 2003;Furuno et al 2004;Abdul Khalil et al 2012;Soltani et al 2013;Dungani et al 2013Dungani et al , 2016Ma et al 2016;Papadopoulos et al 2019). In general, they found that the impregnation of phenol-formaldehyde into wood has resulted in a higher physical, mechanical and dimensional stability properties of wood.…”
Section: Introductionmentioning
confidence: 99%